The Role of Student Interest and Satisfaction on the Performance of University MBKM Policy - DWIANIKA, Dr. Agustine; PURWANTO, Dr. Edi; RAHMAWATI, Elida; PERDANA, Romi Juliani Putri; PRABANDARI, Patricia Keizi (CENTRAL ASIA AND THE CAUCASUS, 2021)
The challenges faced by the accounting study program in implementing the Independent Learning Campus (MBKM) program need to be responded to immediately for the success of the program in the future. This research is needed to determine how much interest, motivation, and satisfaction of students and lecturers in the implementation of MBKM in 2021, as well as to explore corrective information needed. The qualitative method was chosen as the analysis method in order to capture as much information as possible in the research, including constraints and corrections to the implementation of MBKM in 2021. A total of 210 survey data that met the criteria were processed with NVivo and Pivot Table for analysis. The results showed that the implementation of MBKM in the Accounting Study Program is good, but not completely for students of the blended learning program. Most of the students' interests are still focused on internships, student exchange, and entrepreneurship. The motivation of the lecturers is very high, but the conversion of courses in the MBKM curriculum is one of the obstacles. The time between dissemination and program implementation is relatively short, so students have not all prepared themselves to join the program even though they are interested. This research can provide a reference for study programs and related policy makers in the subsequent implementation of MBKM, and overcome problems faced by both students and lecturers so that the role of study programs in bridging efforts to improve the quality of national education can be optimal.